THE ROLE OF TOTAL INCOME INDICATOR IN POVERTY REDUCTION IN UZBEKISTAN - Adashov Gayrat Rustamovich (Labor economics and human capital, 2025)
This article examines the concept of total income of the population, scientific approaches to the issue of its distribution among various strata, poverty reduction in Uzbekistan using the example of state policy in recent years.